LEGALITY LAWS AGAINST THE ROLE OF MOSQUE AS A UNIT MANAGEMENT OF ZAKAT MANAGEMENT (UPZ) A STRATEGIC WAY TO INCREASING WELL-BEING - Hikmah, Nurul (Journal of Islamic Law Studies, 2021)
Zakat is an obligation that should be adopted by a moslem to give a part of their wealth to pass (mus-tahiq) in accordance with islamic syariah. View the community of the existence of the institutions of amil and zakat (LAZ) has not so good, so people want to give (muzakki) more channel until the day own directly to mustahiq. One contributing factor is still less transparent and less well target-ed distribution hearts. Therefore, the need to improve the management of zakat is one solution to make the mosque as a unit zakat (UPZ) based on the collection and distribution of zakat. mosque as a unit zakat management unit has not been fully optimized. This is due to various limitations and constraints that are owned by the agency. However, the mosque has the potential for management in the form of a charity, and of course as a place of worship is very strategic in improving the welfare of pilgrims. The government can give legality aggregator Zakat Unit which is a continuation BAZNAS as a service to the community.